Pemanfaatan Media Buku Bergambar dalam Perkembangan Membaca Awal Anak Usia 4-5 Tahun Melalui Buku Cerita Bergambar di TK Sekolah Alam Banten Darunnisa - Sarkiyah, Sarkiyah; Fadlullah, Fadlullah; Asmawati, Luluk (Universitas Pahlawan Tuanku Tambusai, 2025)
Good reading ability is important in the learning process that affects overall academic achievement. Picture story books were chosen as the main media because they combine text with interesting pictures, so they can stimulate students' interest and imagination. The use of picture story books can effectively improve students' reading skills. The purpose of this study was to determine the improvement of early reading skills through picture story books in children aged 4-5 years at the Banten Darunnisa Nature School Kindergarten. This study was conducted using a survey method. The type of research is quantitative research with a field survey approach. The survey was conducted by giving questionnaires to respondents. The results of the study showed that for children, reading picture story books is a fun experience and stimulates imagination. Reading activities before bed and moments of storytelling together create positive emotional bonds to books and help enrich children's literacy at home. The positive impacts of reading activities are speaking, vocabulary, and learning focus of kindergarten students. Teachers also reveal specific strategies, such as reading together and activities after reading, to increase children's interest in reading in class.